Describing the Use of Freedom Wall in Expressing Students’ Emotion - Balabag, Maria Ceryll; Potane, Joel (Journal of Interdisciplinary Perspectives, 2024)
This study looked into the use of a freedom wall for students' emotional expression. An explanatory sequential mixed-methods research design was used. The study included 30 Grade 11 HUMSS students from a school in Misamis Oriental. A validated survey instrument was used to collect information on students' demographics and opinions. The Freedom Wall's emotional benefits and challenges were investigated using focus group discussions. The results showed that it was a useful venue for expressive arts, thoughts and quotes, emotional expression, and interactive discussions. Students believed that the freedom wall had a favorable impact on their emotional expression and creativity. Thematic analysis indicated three major emotional benefits: emotional relief, confession of feelings, and starting a conversation. Students' perceptions of the Freedom Wall's use were not significantly different when classified by age; nevertheless, gender variations were observed. Female students are more likely to express their feelings openly, which aligns with prior research on gender and emotional expression. Challenges to its use were discovered, including issues about location and privacy, as well as the requirement for physical maintenance. The study indicated that the freedom wall is important for offering emotional release, serving as a confession wall, and initiating student participation. The study shed light on the Freedom Wall's emotional benefits and problems, giving to a better understanding of its role in encouraging emotional expression in schools.